Lower Clergy of Posttridental Epoch in the Light of Bishops’ Visitation Protocols. The Example of Parish of All Saints in Brzeziny - Korban, Tomasz (Vade Nobiscum, tom XXI/2019: Studia z historii gospodarczej, kulturowej i społecznej, 2019)
In the article it had been presented lower clergy of posttridental time in example of Brzeziny parish. This community in Old-Polish period belonged to Cracow diocese. As a main source to research those issue were used acts of canonical visitations. The structure of article is chronological to subsequented periods of priest’s service, who worked in parish from 16th to 18th century. In description of priests included information about their roots, education, priest’s career and also moral attitudes. The picture of Brzeziny parish clergy had been compared with the state of researches about clergy in posttridental times, which assumption was amplification of priest’s role in church community.